DIMENSI SIMBOLIK DAKWAH KULTURAL PADA PENGGUNAAN PAKAIAN HAJI BAGI PENGANTIN DI MANDAILING NATAL - Hasibuan, Susanti (AT-TANZIR: JURNAL ILMIAH PRODI KOMUNIKASI PENYIARAN ISLAM, 2023)
This study aims to unravel the history of the use of hajj clothes worn by brides in Mandailing Natal Regency. This study also uses the interview method with cultural and hatobagon community leaders in the local area where the research is carried out. In the results of his study, hajj clothing is part of the symbolic dimension of the meeting between culture and religion that has been passed down from generation to generation, and this is proven not to deviate from Islamic teachings. It is known that the bride's purpose to wear Hajj clothes worn by the bride is a symbol of prayer, hope, and the sanctity of the marriage itself and the expectation that the bride and groom will perform the Hajj. In addition, leaving for the pilgrimage can raise the image and social strata of the community for those who carry it out.